Pontin52, an interaction partner of β-catenin, binds to the TATA box binding protein - Bauer, Andreas (The National Academy of Sciences, 1998)
β-catenin, the vertebrate homolog of the Drosophila Armadillo protein, has been shown to have dual cellular functions, as a component of both the cadherin-catenin cell adhesion complex and the Wnt signaling pathway. At Wnt signaling, β-catenin becomes stabilized in the cytoplasm and subsequently available for interaction with transcription factors of the lymphocyte enhancer factor-1/T-cell factor family, resulting in a nuclear localization of β-catenin. Although β-catenin does not bind DNA directly, its carboxyl- and amino-terminal regions exhibit a transactivating activity still not well understood molecularly. Here we report the identification of an interaction partner of β-catenin, a nuclear protein designated Pontin52. Pontin52 binds β-catenin in the region of Armadillo repeats 2–5 and, more importantly, also binds the TATA box binding protein. We provide evidence for an in vivo multiprotein complex composed of Pontin52, β-catenin, and lymphocyte enhancer factor-1/T-cell factor. Our results suggest involvement of Pontin52 in the nuclear function of β-catenin.